The Socialization Of Training On Making Dodol From Palm Fruit In Riko Village, Ppu District - Anshory, Jamil (Jurnal Pengabdian Masyarakat Borneo, 2024)
Kelurahan Riko, located in Penajam District, Penajam Paser Utara Regency, East Kalimantan, is predominantly characterized by palm oil plantations. This article discusses a training program on the production of palm oil dodol aimed at enhancing the knowledge and skills of the local community in optimizing the use of palm oil. The methods employed include outreach, socialization, hands-on practice, and direct guidance in making palm oil dodol. The training utilizes a participatory model, where participants are involved in every stage of dodol production, from ingredient selection to processing and final packaging. Evaluation results indicate that the palm oil dodol was well-received by participants, with positive feedback on its taste, color, texture, and aroma. Nutritional analysis reveals that palm oil dodol is rich in energy, fat, carbohydrates, and high in vitamin A, providing added value to the product. This training is expected to maximize the potential of palm oil in Kelurahan Riko and contribute to increasing income and empowering the local economy.